An Information Systems Study on Citibank, N.A. Treasury Services Unit Global Finance Pre-Processing - Medina, John Howard D.; Dela Cruz, Joel C.; Dela Vega, Geraldine C. (College of Engineering, 1994)
Citibank, N.A. is divided into two separate corporate entities, Global Finance (GF) and Global Consumer Banking (GCB). GF handles corporate finance transactions while GCB performs the traditional consumer banking functions. Citibank as a whole has a Treasury Services Unit (TSU) which handles the processing of treasury transactions. By treasury transactions, we mean those which involve money market investments, foreign exchange, and the buying and selling of securities and loans. TSU is responsible for the treasury transactions of both GF and GCB. Due to the difference in the manner by which GF and GCB transactions are handled, this study will cover only the GF segment of operations. GR treasury operations are not as automated as GCB transactions that require minimal manual intervention. This is because GF transactions are difficult to automate because of the special handling instructions for each transaction. Because the information flow in GF treasury operations is essentially on a person-to-person basis, the system tends to fall prey to redundant procedures and documentation. This study will cover the GF Pre-processing section of TSU that performs the bulk of the manual work in transaction processing.